Inter-laboratory evaluation of the EUROFORGEN Global ancestry-informative SNP panel by massively parallel sequencing using the Ion PGM™. (July 2016) - Eduardoff, M.; Gross, T.E.; Santos, C.; de la Puente, M.; Ballard, D.; Strobl, C.; Børsting, C.; Morling, N.; Fusco, L.; Hussing, C.; Egyed, B.; Souto, L.; et al.
Graphical abstract: Highlights: The first custom-built forensic MPS multiplex was built for the EUROFORGEN Global ancestry-informative SNP set analyzed with the Ion PGM™. 125/128 SNPs were successfully incorporated: a 97.6% assay conversion rate. Of 3 substitute SNPs added, one failed to give usable sequence reads. Five-laboratory evaluations of the assay assessed sequencing performance, forensic sensitivity, and mixture detection. Studies of 14 novel populations indicate good informativeness for 5 continental population group differentiations and admixed populations. Analysis of South Asian populations will require extended ancestry-informative SNP panels. Abstract: The EUROFORGEN Global ancestry-informative SNP (AIM-SNPs) panel is a forensic multiplex of 128 markers designed to differentiate an individual's ancestry from amongst the five continental population groups of Africa, Europe, East Asia, Native America, and Oceania. A custom multiplex of AmpliSeq™ PCR primers was designed for the Global AIM-SNPs to perform massively parallel sequencing using the Ion PGM™ system. This study assessed individual SNP genotyping precision using the Ion PGM™, the forensic sensitivity of the multiplex using dilution series, degraded DNA plus simple mixtures, and the ancestry differentiation power of the final panel design, which required substitution of three original ancestry-informative SNPs with alternatives. Fourteen populations that had not been previously analyzed were genotyped using the custom multiplex and these studies allowed assessment of genotyping performance by comparison of data across five laboratories. Results indicate a low level of genotyping error can still occur from sequence misalignment caused by homopolymeric tracts close to the target ignment caused by homopolymeric tracts close to the target SNP, despite careful scrutiny of candidate SNPs at the design stage. Such sequence misalignment required the exclusion of component SNP rs2080161 from the Global AIM-SNPs panel. However, the overall genotyping precision and sensitivity of this custom multiplex indicates the Ion PGM™ assay for the Global AIM-SNPs is highly suitable for forensic ancestry analysis with massively parallel sequencing.